2019
DOI: 10.1177/1753425919840423
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dendritic cell function improves survival in experimental sepsis through immune chaperone

Abstract: Dendritic cells (DCs) are professional Ag-presenting cells that play a critical role in both innate and adaptive immune responses. DCs recognize and respond to bacteria through multiple PRRs, including TLRs. Heat shock protein gp96/grp94 is a master essential chaperone for TLRs in the endoplasmic reticulum. We generated DC-specific gp96-knockout (KO) mice and showed that gp96 KO DCs were unable to respond to multiple TLR ligands. TLR-mediated hyperinflammatory response can lead to sepsis. However, the roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Based on the expression profile of the four ERRGs, we divided the patients with sepsis into two molecular subgroups. After the analysis of immune infiltration characteristics in the two molecular subgroups, the immune-related function was proven to play an essential role in the development of sepsis, which is in concordance with previous literature ( 32 , 33 ). Notably, a remarkable difference was found in 23 kinds of immune cells between the two sepsis subgroups, especially activated B cells, CD4+ T cells, immature dendritic cells, and plasmacytoid dendritic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the expression profile of the four ERRGs, we divided the patients with sepsis into two molecular subgroups. After the analysis of immune infiltration characteristics in the two molecular subgroups, the immune-related function was proven to play an essential role in the development of sepsis, which is in concordance with previous literature ( 32 , 33 ). Notably, a remarkable difference was found in 23 kinds of immune cells between the two sepsis subgroups, especially activated B cells, CD4+ T cells, immature dendritic cells, and plasmacytoid dendritic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Deletion of GRP94/GP96 in different cells induce a hipoinflammatory and autoimmune state via instability in TLR and other molecules; in macrophages generate TLR null cells [45], in dendritic cell reduces the immune response to sepsis [52], while in Treg-cells, the levels of FOXP3 are reduced, inducing IFN-γ and IL-17 overproduction [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of sepsis in animal models and in human patients have shown that the number of DCs was depleted in both lymph and non-lymphoid organs [11]. Using the cecal ligation and puncture (CLP) mouse model of sepsis, the number of CD11c+ DC was found to be lower in the spleen and lymph nodes than that in sham operation groups [12]. In peripheral organs of septic patients, clinical trials have shown that the number of interstitial DCs was remarkably lower than that in non-septic patients [13].…”
Section: Sepsis Can Lead To Reduction In DC Numbermentioning
confidence: 97%